Tracheal bridge for reconstruction of the upper airway in double tracheal stenosis (2020)
Tracheal reconstruction is a complex surgical procedure that requires a well-trained, multidisciplinary team to achieve optimal results. No reviews or case reports involving the use of a healthy tracheal bridge to achieve reconstruction after extensive tracheal resection (greater than 7 cm) are described. We present a clinical case of a patient with double tracheal stenosis secondary to prolonged intubation and tracheostomy for which a healthy, well-vascularized tracheal bridge was used to achieve a tracheal reconstruction without tension. The key point in performing this type of reconstruction is allowing a tension-free cervical and thoracic anastomosis.